Enhancing Pedagogical Deep Learning in Vocational High Schools Through Multimarker Augmented Reality Media - Muh. Ihsan Zulfikar; Muhammad Riska (Information Technology Education Journal, 2025)
This study focuses on creating and assessing an interactive learning media that uses multimarker augmented reality (AR) to improve pedagogical deep learning among vocational students at SMK Gowa. The development process followed the ADDIE model, covering analysis, design, development, implementation, and evaluation phases. The AR application allows students to interact with several 3D virtual objects linked to physical markers, offering an engaging and immersive learning environment suited for vocational subjects. Expert reviews confirmed that the media is accurate, technically sound, and pedagogically appropriate. Testing the application on different smartphones showed it performs well on mid to high-range devices, with minor glitches on lower-end phones that did not affect overall functionality. Feedback from 60 students illustrated strong usability, motivation, and acceptance of the media. Learning assessments before and after the intervention revealed significant gains in student understanding and critical thinking (p < 0.01). Interviews with participants supported these findings, highlighting increased engagement and improved knowledge retention. Overall, the study indicates that AR multimarker media is a practical and effective tool for fostering meaningful and deeper learning in vocational education. The study recommends expanding content, optimizing performance on various devices, and providing teacher support to enhance its use in classrooms. This research adds valuable insights into advancing the role of AR technology in vocational learning to align with modern educational needs.